Um estudo para titulação quimiluminescente em fluxo-batelada com detecção por imagem digital - Leite, Flaviano Carvalho (2016)
The scarcity of chemilumescent (CL) methods based on digital image and flow analyzers is motivation for novel studies, especially when it is not found in literature any paper involving CL titration with digital image. In this work, it is developed the study of a novel methodology for digital image-based quimiluminescent (DIB-CL) titration whose analytical potential is evaluated in determination of Fe2+ in ferrous sulfate syrupe using a flow-batch automatic analyzer. Termed DIB-CL titration, this method employs the own analyte (Fe2+) as catalyst of the oxidation reaction of luminol/H2O2 in alkaline medium and presence of bromide enhancement. After a increment of titrant (KMnO4) to be added to sample in acid medium, a part of Fe2+ is oxidized to Fe3+ and ramaining contributes to generate the CL signal that decreases linearly with the Fe2+ concentration. When the oxidation of Fe2+ is completed, the endpoint of titration is attained and the CL signal remained constant at the level of background radiation with the addition of titrant in excess. Images acquisition is performed by using a webcam coupled to the mixing chamber of flow-batch system. From image obtained before and after each addition of titrant were extracted the R, G, and B values used in order to calculate the analytical reponse, which is defined by vector norm in RGB tri-dimentional space. This norm values are linearly related to the analyte concentration, being employed for building of titration curve where the end point is found by intersection of the two extrapolated straight segments. By applying the paired t-test, titration results of ten samples of syrupe were compared with those obtained by a espectrophotometric method based on analytical curve. No systematic statistic difference has been observed between the both results at the 95% confidence level. DIB-CL system presented a analytical frequency of 18 titrations h-1 and consumes 0.2 mL of luminol and 2.4 mL of sample per titration or analysis. Thus, its performance can be improved by implementing a optimization.